Collaborative Governance in the Unified One-Stop Administration System (Samsat) Based on Digitalization in South Sumatra - Pratiwi, Dina Ayu; Sobri, Kgs M.; Sriati, Sriati; Putra, Raniasa (Universitas Medan Area, 2024)
This study delves into the implementation of Collaborative Governance within the Digitalization-Based One-Stop Integrated Administration System (Samsat) in South Sumatra. It delves into the context of modernizing governmental services through digitalization and the hurdles encountered in achieving collaborative governance within this framework. The research inquiries delve into the efficacy of collaborative governance mechanisms in enhancing service provision and engaging stakeholders within the Samsat system. Employing a mixed-method approach, the study scrutinizes both quantitative data on service performance metrics and qualitative data garnered from interviews and observations. The findings reveal notable enhancements in service efficacy and stakeholder involvement attributed to collaborative governance practices. Nonetheless, challenges such as technological infrastructure constraints and institutional opposition are also highlighted. The study concludes by underscoring the significance of adaptive governance frameworks and stakeholder participation in upholding efficient digitalized administrative systems like Samsat.